Method to Study the Importance of Automobile Industry Chain Based on the Input-Output Model - Junlei Wang; Fan Zhang; Zhaozhao Zhang; Liangliang Wang; Collins Sam Ayipeh (Discrete Dynamics in Nature and Society)
This paper proposes a study based on the importance of the automobile industry chain based on the input-output model (IOM) to verify the importance of the automobile industry chain in the national economy. The available data shows interdependence among various industrial sectors and the automobile industry chain. The same is reflected in the input-output table. The input data is taken from the input-output table (IOTB) of the automobile industry chain. A mathematical model was developed that shows the equilibrium relationship indicating the direct and indirect technical as well as economic links amongst the different sectors. The static model of the IOM was selected. The static model herein reflects the technical and economic correlations amongst the sectors during the same period. The same was applied to analyze and study the contemporaneous production process. 153 fields(variables) were selected to verify multiple economic indicators of the automobile industry chain. The conclusion demonstrates that the auto parts and accessories in the automobile industry chain are in the top 10 among the 153 fields, in terms of their consumption coefficient (CC) and contribution degree. The purpose of the research was to verify the significance of the relationship between various fields which can optimize and upgrade the industrial structure. It also provides a scientific basis for formulating strategies and policies of the relevant industry chain.